Natural history of familial cerebral cavernous malformations: the CCM_Italia cohort study - Lanfranconi, Silvia; Scola, Elisa; Novelli, Deborah; Poggesi, Anna; Pescini, Francesca; Pavanello, Marco; Romano, Ferruccio; D’Alessandris, Quintino Giorgio; Marani, Walter; Signorelli, Francesco; Iaconetta, Giorgio; Torelli, Giovanni; et al. (Frontiers in Neurology, 2026)
BackgroundFamilial cerebral cavernous malformations (fCCMs) are a rare genetic autosomal dominant cerebrovascular disease characterized by multiple cerebral and spinal angiomas. The condition is caused by mutations in KRIT1 (CCM1), CCM2 (malcavernin), or PDCD10 (CCM3) and may lead to intracerebral hemorrhage (ICH) or non-hemorrhagic focal neurological deficits (FNDs), potentially leading to severe disability and even death. To date, little is known about disease progression, and tools to identify patients at higher risk are lacking.MethodsPediatric and adult fCCM patients, whether symptomatic or asymptomatic, will be enrolled and followed annually over a 2-year period. Participants will undergo clinical assessments, blood sampling, and 3 T brain MRI scans at baseline, 12 months, and 24 months. The primary outcome is the new occurrence of symptomatic ICH or FNDs attributable to CCMs over 24 months. Patient characteristics will be assessed for the primary and secondary endpoints and illustrated using Kaplan–Meier curves and Cox proportional hazard regressions. This trial is registered with ClinicalTrials.gov, NCT06983132 and is currently recruiting participants.Discussion/conclusionDespite increasing efforts in basic and clinical research and an improved understanding of the pathogenic mechanisms underlying fCCM, tools to predict disease progression, identify at-risk individuals, and pinpoint effective therapeutic targets are still lacking. This study aims to create the largest Italian cohort of fCCM patients, who will be monitored closely over time to collect data that may help identify risk factors and disease trajectories. The collection of standardized information on clinical and radiological evolution, along with results from circulating biomarkers, will help address the complexities of the disease and may suggest potential reliable markers of disease progression.Clinical trial registrationClinicalTrials.gov, identifier NCT06983132.